P7 A world record for HIV testing. Publicity stunt or effective outreach?. (23rd May 2012) - Jenkins, J; McOwan, A G; McCormack, S; Chislett, L J
Abstract : Background: 1 in 7 MSM in London are HIV positive, 1 of 5 of whom are unaware of this because they have never tested, or acquired HIV since their last test. Our service took the opportunity presented by World AIDS Day to promote the importance of regular HIV testing in MSM by staging a HIV testing world record attempt in a local gay bar. Aims/Objectives: To promote the importance of HIV testing, and to see if the outreach was successful in targeting a less tested population of MSM. Methods: The promotion was determined by the "opportunities to view" key messages. Individuals tested in the bar completed a form collecting age, gender, orientation, time since last HIV test, unprotected anal (UAI) or vaginal sex. Similar information was collected from 100 patients walking into the generic service for an HIV test on the same day. Age groups <25, 26–30, 31–39, >40 were chosen. Results: There were 890 000 opportunities to view the key messages. 467 individuals tested in the gay bar, but only 441 forms were sufficiently complete for this analysis. MSM in the gay bar were younger than the clinic (54% and 44% respectively <30; p=0.027), and more likely to have never tested (18% and 6%; p=0.007). In the gay bar, only 9/89 (10%) of MSM aged 31–39 had never tested, only 2/9 (22%) reporting UAI. This contrasted to the 15%–24% of 54 MSM in the other age groups that had never tested, 60%–77% of whom reported UAI. Only five MSM attending clinic had never tested, 4 (80%) of whom were <25 (see abstract P7 table 1 ). Discussion: As well as promoting the benefits of regular testing to the wider gay community, the event was successful in reaching a less tested, but nonetheless high risk population of MSM, in particular, those <25.